Results of an opinion poll devoted to unification of instructions for interchangeable medicines - N. G. Goloenko; R. I. Yagudina; B. K. Romanov; D. G. Karapetyan; A. Yu. Kulikov; M. V. Protsenko; G. T. Abdrashitova (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The article discusses the results of an opinion poll among healthcare professionals and pharmacists devoted to finding out their attitude to the main problems associated with instructions for medicinal products. It was discovered that there was a lack of consensus on what could be regarded as official and unofficial sources of information about medicinal products. The poll elicited the attitude towards instructions for medicinal products among specialists and, indirectly, the general public, and helped establish a need for introducing changes into the instruction form.